Complexes of lanthanides(iii) with mixed 2, 2′-bipyridyl and 5, 7-dibromo-8-quinolinoline chelating ligands as a new class of promising anti-cancer agents. Issue 5 (2nd May 2019) - Qin, Qi-Pin; Wang, Zhen-Feng; Tan, Ming-Xiong; Huang, Xiao-Ling; Zou, Hua-Hong; Zou, Bi-Qun; Shi, Bei-Bei; Zhang, Shu-Hua
Abstract : MeOMBrQ-Ho induced HeLa cell apoptosis was mediated by inhibition of telomerase activity and dysfunction of mitochondria. Remarkably, MeOMBrQ-Ho obviously inhibited HeLa xenograft tumor growth in vivo. Abstract : Five novel lanthanides(iii ) complexes, [Lu(Me)(MBrQ)2 NO3 ] (MeMBrQ-Lu ), [Ho(MeO)(MBrQ)2 NO3 ] (MeOMBrQ-Ho ), [Ho(Me)(MBrQ)2 NO3 ] (MeMBrQ-Ho ), [La(Me)2 (BrQ)2 NO3 ] (MeBrQ-La ) and [Sm(Me)(BrQ)2 (CH3 OH)NO3 ] (MeBrQ-Sm ), have been synthesized, in which 2, 2′-bipyridyl (4, 4′-dimethyl-2, 2′-bipyridyl (Me) and 4, 4′-dimethoxy-2, 2′-bipyridine (MeO)) and 5, 7-dibromo-8-quinolinoline derivatives (5, 7-dibromo-2-methyl-8-quinolinol (MBrQ-H) and 5, 7-dibromo-8-quinolinol (BrQ-H)) act as the chelating ligands. The in vitro cytotoxic activities of the five Ln(iii ) complexes have been studied with the SK-OV-3/DDP, NCI-H460 and HeLa cancer cells.MeMBrQ-Lu, MeOMBrQ-Ho, MeMBrQ-Ho, MeBrQ-La andMeBrQ-Sm show higher cytotoxicity against the HeLa cells (IC50 values of 1.00 nM–3.45 μM) than cisplatin (13.11 ± 0.53 μM). In particular, theMeOMBrQ-Ho andMeMBrQ-Ho complexes exhibit superior cytotoxic activity, with IC50 values at 1.00 ± 0.34 nM and 125.00 ± 1.08 nM. We further demonstrate thatMeOMBrQ-Ho andMeMBrQ-Ho inhibit the proliferation of HeLa cells by inhibiting telomerase and targeting mitochondria to induce DNA damage-mediated apoptosis. In addition, MeOMBrQ-Ho significantly inhibits tumor growth with a tumor growth inhibition rate (IR) of 50.8% in a HeLa mouse xenograft model. Taken together, MeOMBrQ-Ho is a novel lanthanide(iii ) complex with promising antitumor activity.